Bi-fuel NGVM engine emission results based on non-loaded system operation - Mohsin, Rahmat; Yaacob, Zulkifli; Abdul Majid, Zulkefli; Ashraf, Shameed (Faculty of Chemical and Natural Resources Engineering,Universiti Teknologi Malaysia, 2009)

(untitled)
Alternative fuels for the internal combustion engines are introduced as an improved fuel over mainstream conventional fuels such as petrol and diesel. Compressed Natural Gas (CNG) is the most successful and widely used alternative fuels that helps mitigate emission problem caused by vehicles. Mainstream fuelled vehicles are fitted with a conversion kit to enable the operation with CNG, these converted vehicles are called Natural Gas Vehicles. A bi-fuel engine test rig was fabricated using a 1500cc 12 Valve engine fitted with a Landi Renzo conversion kit enabling operations on petrol and natural gas. This test rig was used to conduct experiments to obtain the fuel consumption and the corresponding exhaust emission quality. The results obtained were compared with the actual data of NGV taxi fitted with Tartarini conversion kit for validation purpose. The findings from this experimental rig are used as a comparison between the use of petrol and natural gas as fuel for vehicles. The results clearly prove that the use of natural gas provides improved exhaust emission at lower cost